Aнгли хэлний нэрийн бүлгийн орчуулгын алдаанд хийсэн дүн шинжилгээ (ШУС, гадаад хэлний орчуулга хөтөлбөрийн оюутны жишээгээр): An Error Analysis on the English Noun Phrase Translation (In the example of the foreign language translation students at the School of Arts and Sciences) - Ts., Oyunsuren; R., Batsuren (Mongolian Journal of Foreign Languages and Cultures, 2023)
The purpose of the present research study was to carry out an error analysis on the English noun phrase translation. In this respect, we investigated the errors in a corpus of 8 versions of mini tests translated by 16 intermediate students of the School of Arts and Sciences at NUM. The instrument used for this study was students’ noun phrase translations in the English language. All the errors related to the noun phrase in this article were identified, described, explained and evaluated according to Stephen Pit Corder’s taxonomy. Specifically, we aimed to identify the source of the errors. The findings demonstrated that the source of students' errors could be explained by interlingual and intralingual transfers. Furthermore, we wrote a recommendation for the students to refine their language proficiency.